Doppler ultrasound - a valid and reliable tool to assess spondyloarthritis - Falcão, Sandra (2012)
Enthesitis is the hallmark of spondyloarthritis and is observed in all subtypes. Namely, a wide information on spondyloarthritis abnormalities, including synovitis, bursitis, tendinitis, enthesitis and cortical bone abnormalities (erosions and enthesophytes), can be efficiently perceived by ultrasound power Doppler. Furthermore, several studies on imaging of enthesis showed that imaging techniques are better than clinical examination to detect pathology at asymptomatic enthesis. Vascularized enthesitis detected by ultrasound power Doppler appears to be a valuable diagnostic tool to confirm spondyloarthritis diagnosis. This article focuses on the validity and reliability of ultrasound enthesitis assessment in the management of spondyloarthritis patients.